JOHN PHILOPONUS CONTRA ARISTOTLE: The Emergence of Consciousness in Light of Contemporary Cosmology and Philosophy - Ventureyra, Scott (Science et Esprit)

(untitled) (Collège universitaire dominicain, Ottawa, 2020)
The objective of this paper is to examine the thought of John Philoponus contra Aristotle, as it pertains to consciousness and its emergence, in light of both contemporary cosmology and philosophy. It will be argued that in an eternal universe the emergence of consciousness is an impossibility. The inspiration for this line of reasoning is found in Philoponus’ sixth century arguments against Aristotle on the eternity of the world. It will be shown that much of Philoponus’ argumentation is corroborated by contemporary cosmology and philosophy.